Sensitivity of transvaginal ultrasound and hysterosonography compared with hysteroscopy in infertility patients - Hilario, Roly (2015)
Objective: To determine the diagnostic sensitivity of transvaginal ultrasonography and sonohysterography compared with hysteroscopy in patients with infertility. Design: Descriptive study. Setting: Procrear Fertility Clinic, Lima, Peru. Participants: Women with infertility. Methods: Between January and December 2 013 patients studied for infertility underwent surgical hysteroscopy; corresponding transvaginal ultrasound and hysterosonography prior to surgery were analyzed for most frequent diagnoses and sensitivity of the studies. Analysis was done using SPSS 15 software. Main outcome measures: Sensitivity of hysteroscopy, transvaginal ultrasound, and hysterosonography. Results: One hundred and eighteen surgical hysteroscopies were performed. Prior transvaginal ultrasound had sensitivity of 44.9% (53/118) for any abnormalities in regards to hysteroscopy, and sonohysterography had sensitivity of 95.7% (113/118). Hysteroscopic findings were endometrial polyp in 74 (62.7%), uterine synechiae in 30 cases (25.4%), submucosal fibroids in 12 (10.2%) and other in 2 cases (1.7%). In relation to uterine synechiae, transvaginal ultrasound alone had sensitivity of 10% and hysterosonography sensitivity of 86.6%, and transvaginal ultrasound had sensitivity of 45.3% and hysterosonography sensitivity of 93% for endometrial polyps along with submucosal fibroids. Conclusions: Hysterosonography had better sensitivity than transvaginal ultrasonography for detecting endometrial pathology affecting fertility. It also assessed endocervical permeability, suggesting its value in the study of women with infertility.